(untitled) (مجلة العلوم الشاملة, 2025)
Type 2 Diabetes Mellitus (T2DM) is a prevalent metabolic disorder associated with dyslipidemia, which significantly increases the risk of cardiovascular diseases. Statin therapy is commonly prescribed to manage lipid profiles in T2DM patients. However, the comparative efficacy of different statins in this population remains underexplored, particularly in specific regional contexts such as Tarhuna City, Liby